2018
DOI: 10.1002/slct.201703081
|View full text |Cite
|
Sign up to set email alerts
|

TiO2‐Graphene Nanocomposites for Effective Photocatalytic Degradation of Rhodamine‐B Dye

Abstract: The hazardous Rhodamine-B dye is photocatalytically degraded by anatase TiO 2 and its graphene nanocomposites. These are prepared by a simple electrochemical anodic dissolution of pure titanium in graphene oxide solution, here particle size is tuned by current variation. The structural, morphological and optical properties of these composites are studied by X-ray diffraction, UV-visible spectroscopy, field emission SEM, high resolution TEM and XPS. The photocatalytic activity of Rhodamine-B in water is studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 45 publications
0
16
0
1
Order By: Relevance
“…The 2θ value of 25, 37.8, 48.1, 54.4, 62.5, and 69 o responds to the crystallographic planes of (1 0 1), (0 0 4), (2 0 0), (1 0 5), (2 0 4), and (2 2 0), respectively, which expressed the TiO2 anatase phase (JCPDS no.21-1272) holding up the samples. [12,13] The XRD data indicated the anchoring of the TiO2 crystalline particles onto rGO sheets in the binary composite structure. Raman spectra of rGO and TiO2/rGO materials were shown in figure 1c.…”
Section: Characterization Of Nanocompositesmentioning
confidence: 98%
“…The 2θ value of 25, 37.8, 48.1, 54.4, 62.5, and 69 o responds to the crystallographic planes of (1 0 1), (0 0 4), (2 0 0), (1 0 5), (2 0 4), and (2 2 0), respectively, which expressed the TiO2 anatase phase (JCPDS no.21-1272) holding up the samples. [12,13] The XRD data indicated the anchoring of the TiO2 crystalline particles onto rGO sheets in the binary composite structure. Raman spectra of rGO and TiO2/rGO materials were shown in figure 1c.…”
Section: Characterization Of Nanocompositesmentioning
confidence: 98%
“…Graphene sheets, nanotubes and nanoparticles with a higher specific surface area and excellent electronic properties can be used as a photocatalytic support for TiO 2 to improve the photocatalytic activity [29]. Gunnagol et al [30] obtained TiO 2 -graphene nanocomposites to study the photocatalytic degradation of Rhodamine B under UV irradiation (degradation yield 98%) and under visible light irradiation (degradation yield 87.19%), and reported that this activity was reached due to the large surface area, providing a greater number of surface active sites in the materials. Yang et al [31] successfully prepared TiO 2 /graphene porous composites for methylene blue photodegradation, compared composites results to TiO 2 Degussa P25 and verified that the composites increased light-absorbing capacity accelerating the separation of electrons and holes, suppressing the charge recombination owing to graphene properties.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, dye molecules such as methylene blue are unable to release electrons to the CB. [49][50][51][52] Furthermore, the existence of numerous functional groups, a large surface area, and a porous structure created an oxygen vacancy in the reaction interface, which acts as an active site (induced bandgap) for capturing electrons from the conduction band at the heterojunction interface. Thus, the hole-electron recombination was delayed and hence the continuous flow of electrons from the conduction band to the induced bandgap prevents dye from releasing electrons.…”
Section: Degradation Mechanism By Dye Sensitizationmentioning
confidence: 99%